Identifikasi Kemampuan Berpikir Komputasi Siswa SMP - Amalia, Khoirunnisaa Fadhilah; Nurcahyono, Novi Andri; Lukman, Hamidah Suryani; Bahasa Indonesia, Bahasa Indonesia (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
At this time, computational thinking ability is very important because it can help humans in achieving success in the world of work and society is getting bigger. This preliminary study aims to identify and explore the computational thinking skills of junior high school students and the factors that influence them. The research method used was mixed methods by giving 3 description questions on linear function material that can measure computational thinking ability to 35 class IX students in one of the junior high schools in Sukabumi. The results showed that the highest score achieved by students was 91.67 while the lowest score was 16.67. The average score was 58.33 with 20 students above average and 15 students below average. The median test score was 58.33 with the modes being 44.44 and 61.11. After analyzing each student's answer, it was found that the computational thinking ability of junior high school students was at a low level. The test results stated that students were only capable of the problem decomposition and algorithm stages, not yet to the stages of pattern recognition and abstraction. Students tend to perform calculations directly after breaking down the problem into smaller parts and writing down sequential steps to solve the problem. This shows that mathematics learning in schools today is still lacking in directing students to computational thinking skills.